Capillary rarefaction during bed rest is proportionally less than fibre atrophy and loss of oxidative capacity. Issue 6 (13th September 2022) - Hendrickse, Paul William; Wüst, Rob C.I.; Ganse, Bergita; Giakoumaki, Ifigeneia; Rittweger, Jörn; Bosutti, Alessandra; Degens, Hans
Abstract: Background: Muscle disuse from bed rest or spaceflight results in losses in muscle mass, strength and oxidative capacity. Capillary rarefaction may contribute to muscle atrophy and the reduction in oxidative capacity during bed rest. Artificial gravity may attenuate the negative effects of long‐term space missions or bed rest. The aim of the present study was to assess (1) the effects of bed rest on muscle fibre size, fibre type composition, capillarization and oxidative capacity in the vastus lateralis and soleus muscles after 6 and 55 days of bed rest and (2) the effectiveness of artificial gravity in mitigating bed‐rest‐induced detriments to these parameters. Methods: Nineteen participants were assigned to a control group (control, n  = 6) or an intervention group undergoing 30 min of centrifugation ( n  = 13). All underwent 55 days of head‐down tilt bed rest. Vastus lateralis and soleus biopsies were taken at baseline and after 6 and 55 days of bed rest. Fibre type composition, fibre cross‐sectional area, capillarization indices and oxidative capacity were determined. Results: After just 6 days of bed rest, fibre atrophy (−23.2 ± 12.4%, P  < 0.001) and reductions in capillary‐to‐fibre ratio (C:F; 1.97 ± 0.57 vs . 1.56 ± 0.41, P  < 0.001) were proportional in both muscles as reflected by a maintained capillary density. Fibre atrophy proceeded at a much slower rate between 6 and 55 days of bed rest (−11.6 ± 12.1% of 6 days, P  = 0.032) and was accompanied by a 19.1% reduction in succinate dehydrogenase stain optical density ( P  < 0.001), without any further significant decrements in C:F (1.56 ± 0.41 vs. 1.49 ± 0.37, P  = 0.459). Consequently, after 55 days of bed rest, the capillary supply–oxidative capacity ratio of a fibre had increased by 41.9% ( P  < 0.001), indicating a capillarization in relative excess of oxidative capacity. Even though the heterogeneity of capillary spacing (LogR SD) was increased after 55 days by 12.7% ( P  = 0.004), tissue oxygenation at maximal oxygen consumption of the fibres was improved after 55 days bed rest. Daily centrifugation failed to blunt the bed‐rest‐induced reductions in fibre size and oxidative capacity and capillary rarefaction. Conclusions: The relationship between fibre size and oxidative capacity with the capillary supply of a fibre is uncoupled during prolonged bed rest as reflected by a rapid loss of muscle mass and capillaries, followed at later stages by a more than proportional loss of mitochondria without further capillary loss. The resulting excessive capillary supply of the muscle after prolonged bed rest is advantageous for the delivery of substrates needed for subsequent muscle recovery.